2017
DOI: 10.3390/app7060583
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Evaluation and Application of Snowmelt Performance of Anti-Icing Asphalt Pavement

Abstract: This paper presents a quantitative estimation of anti-icing asphalt mixture snow-melting performance and provides the application guidance for the mixture under study. The regression model of snowmelt quality evolution was established and experimentally verified for different values of snowfall intensity, temperature and blending content of anti-icing filler. The deicing performance of anti-icing asphalt mixtures was evaluated via the impact load tests. The results obtained indicate that the application temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…And Chen found that adding anti-stripping agent to the salt storage asphalt mixture, which could improve the water stability effectively [84]. In comparison, the effect of inorganic anti-peeling agent was better.…”
Section: Road Performance Improvement Measuresmentioning
confidence: 99%
“…And Chen found that adding anti-stripping agent to the salt storage asphalt mixture, which could improve the water stability effectively [84]. In comparison, the effect of inorganic anti-peeling agent was better.…”
Section: Road Performance Improvement Measuresmentioning
confidence: 99%
“…In the 1960s, Germany, Switzerland, Japan, and other developed countries took the lead in developing the technology of snow/ ice removal on salt-storage asphalts pavement. 8 Various saltstorage additives have been developed with a series of names such as WinterPave, 9 Verglimit, 10 Iceguard, 11 Maflon, 12 IceBane, 13 ZFSY, 14 and Grikol, 15 etc. Most of these antiicing products contain 30−70 wt % NaCl, CaCl 2 , or MgCl 2 active ingredients with a particle size less than 5 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Shan et al conducted studies measuring pavement wettability after applying a hydrophobic coating, changes in stone absorption rates, and the length and density of cracks in the ice layer following the impact of a steel ball [22]. Zheng et al conducted an analysis and evaluation of the deicing coating's performance from various perspectives, including anti-ice and snow performance, durability of the coating materials, and impact on pavement skid resistance [23]. Wu et al developed a regression model for long-term snow melting performance and provided a calculation formula for determining the precipitation amount of additives on self-melting asphalt pavement in different regions of the country [24].…”
Section: Introductionmentioning
confidence: 99%